2000
DOI: 10.1023/a:1002891517101
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Quantitative cytochemical assay showed that single injection of delta sleep-inducing peptide increased monoamine oxidase activity (substrates: serotonin and tryptamine) in the caudate and accumbens nuclei and glutamate dehydrogenase activity in the hippocampus of stress-resistant Wistar rats chronically treated with L-DOPA. Enzyme activities in the sensorimotor cortex did not change. Delta sleep-inducing peptide had no effects on acetylcholine esterase and aminopeptidase activities in the brain of Wistar rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A negative effect of emotional stress on subsequent course of brain ischemia eliminating individual differences and sensitivity to this condition and determining 90% mortality was also demonstrated [2]. We previously showed that long-term administration of L-DOPA (Madopar-125) to rats with low locomotor activity in the open field determined more pronounced changes in cytochemical parameters of protein metabolism (inhibition of aminopeptidase activity) in the sensorimotor cortex, caudate nucleus, and nucleus accumbens [4]. The hippocampus plays a role in triggering the brain response to L-DOPA treatment, because activity of glutamate dehydrogenase, the enzyme involved into not only oxidative processes in cells and protein metabolism, but also into metabolism of glutamate as an excitatory neurotransmitter, locally increases in hippocampal neurons in rats with low locomotor activity in the open field.…”
mentioning
confidence: 99%
“…A negative effect of emotional stress on subsequent course of brain ischemia eliminating individual differences and sensitivity to this condition and determining 90% mortality was also demonstrated [2]. We previously showed that long-term administration of L-DOPA (Madopar-125) to rats with low locomotor activity in the open field determined more pronounced changes in cytochemical parameters of protein metabolism (inhibition of aminopeptidase activity) in the sensorimotor cortex, caudate nucleus, and nucleus accumbens [4]. The hippocampus plays a role in triggering the brain response to L-DOPA treatment, because activity of glutamate dehydrogenase, the enzyme involved into not only oxidative processes in cells and protein metabolism, but also into metabolism of glutamate as an excitatory neurotransmitter, locally increases in hippocampal neurons in rats with low locomotor activity in the open field.…”
mentioning
confidence: 99%